The Existence of the Unjung-Unjungan Tradition (A Study in Rambatan Kulon Village, Lohbener District, Indramayu Regency) - Didik Himmawan; Abduloh; Sandy Kurniawan (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2024)
Tradition and culture in Islam are the result of reason, reason, creativity, intention and human work which are based on human values. Islam really respects human reason, the results of reason, reason, taste and intention that have been selected by universal human values ​​to develop into a civilization. This article discusses the existence of the Ujung-unjungan tradition in Rambatan Kulon village, where the people still believe in and still apply good cultures. This article aims to obtain information about the existence of the Ujung-Ujungan Tradition (Study in Rambatan Kulon Village, Lohbener District, Indramayu Regency. The methodology in this article is qualitative, using an observation and interview approach. The results of this research are the Ujung-unjungan tradition in Rambatan Kulon Village, Lohbener District Indramayu Regency has been held since our ancestors, it is a good tradition when viewed from the perspective of humans as social creatures, because the series of events involve all elements in society, working together and connecting with all levels of society, which is a good tradition that needs to be preserved such as eating together, getting together, staying in touch, pilgrimage, tahlilan, and gathering with family to build closeness together, preserving traditions such as wayang kulit, plays, traditional Indramayu reog arts and other good traditions, because they contain elements of the spirit of mutual cooperation and strengthening solidarity between citizens. And bad things need to be avoided, such as the practice of gambling, drinking and other activities that violate Islamic law and the norms that apply in society.